Participation based intelligent manufacturing : customisation, costs, and engagement - Mockevičienė, Birutė (Emerald Publishing Limited, 2024)
Manufacturing companies around the world, large and small, in developed and developing regions, tend to suffer from the inefficiencies of a cost-simulated, early pricing process for new products. Often, however, solutions to the complex challenges of the manufacturing industry lie at the intersection of social science and technology, where intelligent manufacturing plays a crucial role. Providing a deep review of innovative scientific technologies and knowledge, this edited collection delves into cost-cutting technologies in manufacturing planning processes that combine with social technologies to stimulate the development of organisational innovations. Chapters explore the solutions that artificial intelligence, data science, and knowledge management systems provide in order to resolve the problems posed by early cost estimation. Drawing on detailed examples from the furniture manufacturing businesses, they offer a new way of industrial thinking with transformative implications for the greater manufacturing industry. Presenting ready-to-use, innovative solutions based on scientific evidence, Participation Based Intelligent Manufacturing is this decade's essential guide for navigating, streamlining and revitalising the industrial field.
Includes index.
Keywords: Business planning.; Business & Economics -- General.; Business strategy.; Business and Management.; elektronické knihy; electronic books